1994
DOI: 10.1104/pp.106.4.1313
|View full text |Cite
|
Sign up to set email alerts
|

Vacuolar-Type H+ -ATPases Are Associated with the Endoplasmic Reticulum and Provacuoles of Root Tip Cells

Abstract: To understand the origin of vacuolar H+-ATPases (V-ATPases) and their cellular functions, the subcellular location of V-H+-ATPases was examined immunologically in root cells of oat seedlings. A V-ATPase complex from oat roots consists of a large peripheral sector (V,) that includes the 70-kD (A) catalytic and the 60-kD (6) regulatory subunits. The soluble V1 complex, thought to be synthesized in the cytoplasm, is assembled with the membrane integral sector (V.) at a yet undefined location. In mature cells, VAT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
49
1

Year Published

1997
1997
2018
2018

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 95 publications
(61 citation statements)
references
References 37 publications
11
49
1
Order By: Relevance
“…Although we have shown that expression of the DET3-GFP fusion is able to rescue the det3 phenotype, we cannot exclude that only a subfraction of the detected protein is functional. However, our observations concerning its cellular localization are in good agreement with results obtained by other groups using immunocytochemistry (Herman et al 1994) and fractionation studies (Rouquie et al 1998). …”
Section: Expression and Cellular Localization Of Det3supporting
confidence: 82%
“…Although we have shown that expression of the DET3-GFP fusion is able to rescue the det3 phenotype, we cannot exclude that only a subfraction of the detected protein is functional. However, our observations concerning its cellular localization are in good agreement with results obtained by other groups using immunocytochemistry (Herman et al 1994) and fractionation studies (Rouquie et al 1998). …”
Section: Expression and Cellular Localization Of Det3supporting
confidence: 82%
“…However, it is not clear how coniferin stored in vacuoles is moved to the cell wall. V-ATPase is not localized solely to mature vacuoles but also to small vesicles, Golgi, and the trans-Golgi network (TGN; Herman et al, 1994;Schumacher and Krebs, 2010). Our data show that coniferin transporter is enriched in the light membrane fraction by Suc density gradient fractionation (Fig.…”
Section: Discussionmentioning
confidence: 71%
“…1 and 2). The vacuolar H + -ATPase and PPiase have both been reported to be present in membranes other than the vacuolar membrane (Herman et al, 1994;Robinson, 1996), but the main location of both of these proteins is the vacuolar membrane. The fact that both of these markers were used must have reduced the risk of incorrectly identifying the vacuolar membrane to a minimum.…”
Section: Discussionmentioning
confidence: 99%